Marcadores bioquímicos da Síndrome Metabólica em indivíduos - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The cardiovascular diseases become up main causes of mortality and obesity in the world. Despite of several preventive measures, these are still insufficiently and deathly index due cardiovascular diseases recurrences continue increasing as such in developed countries as development countries. Studies demonstrated significant the association both uric acid levels and inviduals components of metabolic diseases, but the prevalence ambit of metabolic syndrome using recently definitions among hypeuricemic peoples is unknown and many intrinsic factors in both situations remain unclear. The present study evaluated relations among metabolic syndrome and antiinflamatory markers in hyperuricemic individuals. It have been 499 peoples attended in the Clincal Analyses laboratory of Getulio Vargas University Hospital in Manaus – Amazonas – Brazil, with range age 15-45, above sexs, were grouped into four groups : 1 Control (n=75) 2 Pre - Metabolic Syndrome (n=226) 3.Metabolic Síndrome (129) 4.Hyperuricemic (n=68). For the evaluation of oxidative stress levels of total thiols , total antioxidant capacity , total capacity oxidant , glutathione peroxidase and malondialdehyde were measured. For the evaluation of the inflammatory process parameters C-reative protein, alpha 1- glycoprotein , ferritin , tryptophan and kynurenine were evaluated . In this study, metabolic syndrome was estimated at 34 % and the obesity range was 28 % . Biochemical markers showed statistical differences between the groups, being higher in hyperuricemic subjects with metabolic syndrome than in the control group and metabolic síndorme isolated . The hyperuricemic participants with metabolic syndrome had the following changes compared to the control group: increased inflammatory marker ( kynurenine ) and antioxidant ( glutathione peroxidase ) decreased. Regarding the group with metabolic syndrome only, these parameters were less pronounced . No statistical difference between groups of malondialdehyde was observed. Correlation analysis showed that high levels of kynurenine was positively related to waist, glucose and ferritin in patients with metabolic syndrome who were not found in the control group Thus, hyperuricemic subjects with metabolic syndrome may have a higher inflammation status and a higher level of oxidative stress. A higher inflammation status was correlated with decrease in the levels of antioxidant enzymes and increase in risk metabolic syndrome .Therefore, these results suggest that kynurenine and glutathione peroxidase can be used as a biomarker for cardiovascular disease in patients hyperuricemic with metabolic syndrome .
Keywords: Síndrome metabólica; Hiperuricemia; Doenças cardiovasculares; Metabolic syndrome; Hyperuricemia; Cardiovascular disease; CIÊNCIAS DA SAÚDE: FARMÁCIA